A study on perceived knowledge, attitude, and behaviour towards acceptance of the Covid-19 vaccine among the people of Sabah - Lai, Che Ching; Haslinda Hasan; Syahrudin Ag Ahmad; Intan Soliha Ibrahim; Aisah Meri (Global Academic Excellence, 2022)
The Malaysian government vaccination drive to curb the Covid-19 virus has received with mixed responses from the citizen. To manage the vaccination drive, the government urge the people to register their interest using a mobile apps called MySejahtera. However, in Sabah, the state located in Borneo Island the response was very slow. Therefore, this study aims to uncover the perceived knowledge, attitude, and behaviour among the people in Sabah toward the Covid-19 vaccine. It also aimed to find out the proportion of people who accept, refuse and indecisive in getting the vaccine. A survey was administered to 985 respondents inclusive of citizen and the undocumented from Sabah’s three largest urban centres. Both data collection procedures were conducted throughout March 2021.The result shows the overall perceived knowledge, attitudes and perceived behaviour among respondents were positive towards the vaccine. Information seeking and sharing behaviour about vaccines among the respondent are on the high side. Only 50.3% of the respondents indicated that they are willing to receive the vaccine, 27% are indecisive and 22.7% indicated refuse. Female respondents are more positive towards the vaccines. There is no significant difference between age group as well as between the economic background. The study implies that there was a need to have an additional key message on the content, development and how the vaccines work. Specific key messages for the undocumented need to be formulated to increase their overall experience with the vaccine. An investment in Interpersonal communication network was needed in engaging the fence-sitter.